Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Produktivitas Karyawan Pada Kedai Nanu di Badung - Cyntiadewi, Putu Ari Krisna; Suartina, I Wayan; Sasmita Dewi, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The success of the company depends on the productivity of its employees so that productivity is a very important consideration in achieving the goals of the organization. The purpose of this study was to determine the effect of work discipline and work motivation on employee productivity at Kedai Nanu in Badung. The entire population was involved as a sample with a total of 34 respondents. The data analysis technique used multiple linear regression analysis. Based on the results of the analysis, it was found that work discipline and work motivation had a positive and significant effect on employee productivity at Kedai Nanu in Badung partially and simultaneously. Suggestions in this study are to maintain and improve employee productivity by paying attention to work discipline and work motivation factors.